Coastal Geomorphological Context and Structural Assessment of Mangrove Ecosystems on Bangkobangkoang Island, South Sulawesi, Using Unmanned Aerial Vehicle (UAV) Photogrammetry - Askiyamin Alimuddin; Muhammad Kamal; Bachtiar Wahyu Mutaqin (Universitas Lambung Mangkurat, 2026)
Mangrove forests are important coastal ecosystems under increasing anthropogenic threat, necessitating accurate and efficient monitoring, particularly on resource-limited small islands like Bangkobangkoang Island in Pangkajene and Islands Regency, South Sulawesi. This study aims to fill the gap in detailed inventory data by using Unmanned Aerial Vehicle (UAV) photogrammetry along with field surveys and Geographic Information Systems (GIS) to map out where the mangroves are and assess their height on the island, considering its unique coastal shape. The study found six types of mangroves: Rhizophora stylosa, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, Avicennia marina, and Lumnitzera racemosa. Mapping the area showed that the most common mangroves were Rhizophora stylosa, covering 5.79 hectares, and Rhizophora apiculata, covering 4.06 ha, with Sonneratia alba covering 0.34 ha. A structural assessment showed that the height of the mangroves changed across the island, with taller stands in the north. The tallest Rhizophora apiculata trees were 14.94 meters tall, while the tallest Rhizophora stylosa and Sonneratia alba trees were 5.88 meters and 4.84 meters tall, respectively. The average heights of Rhizophora apiculata, Rhizophora stylosa, and Sonneratia alba are 5.65 meters, 3.12 meters, and 2.26 meters, respectively. Using detailed data from high-resolution UAVs gives us precise and complete information about the area, creating a strong foundation for conservation and management plans for small island mangrove ecosystems.